2014
DOI: 10.1111/nmo.12357
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond perceptions: internalized stigma in the irritable bowel syndrome

Abstract: Patients with IBS report both perceived and IS with alienation most reported. However, IS significantly predicts several patient outcomes when controlling for PS. Cultural and illness traits may influence how stigma is perceived and internalized. Future research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 66 publications
2
58
0
Order By: Relevance
“…Research in IBS and IBD has previously been conducted for perceived and internalized stigma but is lacking in the area of enacted stigma . One recent study of young adults with IBD found that the experience of perceived and enacted stigma frequently leads to patients choosing not to disclose or to attempt to conceal these conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Research in IBS and IBD has previously been conducted for perceived and internalized stigma but is lacking in the area of enacted stigma . One recent study of young adults with IBD found that the experience of perceived and enacted stigma frequently leads to patients choosing not to disclose or to attempt to conceal these conditions .…”
Section: Introductionmentioning
confidence: 99%
“…While there are similar findings in the IBS population 30 , one study investigating a variety of chronic illnesses found anticipated stigma resulted in less healthcare utilization 13 . The nature and newness of EGIDs may explain the increase in healthcare utilization.…”
Section: Discussionmentioning
confidence: 74%
“…The negative impact of perceived stigma on HRQOL and other psychosocial variables has been noted throughout literature in IBS and IBD 2730 . Therefore, we anticipated the relationship between perceived stigma and HRQOL in people with an EGID to be similar.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations